Application of prebiotics in fat free Greek yogurt: physicochemical, texturometric and sensory evaluation (Research, Society and Development, 2022)
Yogurt is one of the most popular fermented dairy products and an excellent vehicle for delivering functional ingredients such as prebiotics. In yogurts, prebiotics can act as a substrate for the growth of the intestinal microbiota, improving gastrointestinal functions and the immune system. Given this context, the present work aimed to evaluate the influence of the addition of three prebiotics such as lactulose, resistant dextrin and fructo-oligosaccharides up to a concentration of 5 %, on the physicochemical, texturometric and sensorial characteristics of Greek yogurt through a Simplex-Lattice Mix Planning. The dependent variables studied were: dry extract, total titratable acidity, pH, firmness and acceptance. Through the Response Surface methodology, it was observed that the independent variables showed statistically significant effects (p